The adrenal cortex after estradiol or daidzein application in a rat model of the andropause: Structural and hormonal study - Ajdžanović, Vladimir; Miler, Marko; Živanović, Jasmina; Filipović, Branko; Šošić-Jurjević, Branka; Popovska-Perčinić, Florina; Milošević, Verica (Elsevier BV, 2020)
Daidzein application may represent an effective and less harmful alternative to indicated, classical estrogenization of ageing men. The aim of this study was to perform structural and hormonal analysis of the adrenal cortex, after estradiol or daidzein supplementation in a rat model of the andropause. Material and methods: Middle-aged Wistar rats were divided into sham operated (SO; n = 8), orchidectomized (Orx; n = 8), estradiol treated orchidectomized (Orx + E; n = 8) and daidzein treated orchidectomized (Orx + D; n = 8) groups. Estradiol (0.625 mg/kg b.m./day) or daidzein (30 mg/kg b.m./day) were administered subcutaneously for three weeks, while the SO and Orx groups received the vehicle alone. Set objectives were achieved using stereology, histochemistry/immunohistochemistry, immunoassays and ultrastructural analysis. Results: Both estradiol and daidzein treatment significantly increased volumes of the zona glomerulosa cell and nuclei, but decreased circulating aldosterone levels. Estradiol markedly increased volumes of the zona fasciculata cell and nuclei in parallel with significant decrease of the adrenal tissue level of corticosterone, while daidzein significantly decreased both the adrenal and circulating levels of corticosterone. Serum DHEA level and volumes of the zona reticularis cell and nuclei significantly increased upon estradiol treatment, whereas daidzein even stronger increased the circulating level of DHEA. Shunting of the corticosteroidogenesis pathways towards adrenal androgens production, after the treatments, corresponded to the ultrastructural findings and zonal capillary network rearrangements. Conclusions: Given the coherence of its effects and relative safety, daidzein could be the remedy of choice for the treatment of ageing-caused androgen deprivation and the hypothalamo-pituitary-adrenal axis hyperfunction/related metabolic issues in males.